Fast autooxidation of a bis-histidyl-ligated globin from the anhydrobiotic tardigrade, Ramazzottius varieornatus, by molecular oxygen. (22nd January 2021) - Kobayashi, Kazuo; Kim, JeeEun; Fukuda, Yohta; Kozawa, Takahiro; Inoue, Tsuyoshi
Abstract: Tardigrades, a phylum of meiofaunal organisms, exhibit extraordinary tolerance to various environmental conditions, including extreme temperatures (−273 to 151°C) and exposure to ionizing radiation. Proteins from anhydrobiotic tardigrades with homology to known proteins from other organisms are new potential targets for structural genomics. Recently, we reported spectroscopic and structural characterization of a hexacoordinated haemoglobin (Kumaglobin [Kgb]) found in an anhydrobiotic tardigrade. In the absence of its exogenous ligand, Kgb displays hexacoordination with distal and proximal histidines. In this work, we analysed binding of the molecular oxygen ligand following reduction of haem in Kgb using a pulse radiolysis technique. Radiolytically generated hydrated electrons ( e aq − ) reduced the haem iron of Kgb within 20 µs. Subsequently, ferrous haem reacted with O2 to form a ferrous-dioxygen intermediate with a second-order rate constant of 3.0 × 10 6  M −1  s −1 . The intermediate was rapidly (within 0.1 s) autooxidized to the ferric form. Redox potential measurements revealed an E ʹ0 of −400 mV (vs. standard hydrogen electrode) in the ferric/ferrous couple. Our results suggest that Kgb may serve as a physiological generator of O2 ▪ − via redox signalling and/or electron transfer. Graphical Abstract: